Mechanical and physical properties of particleboard from untreated and treated kenaf particles / Nur Liyana Aifa Mahammad Asri … [et al.] - Mahammad Asri, Nur Liyana Aifa; Mohamed Anwar, Ainil Idzaty; Najib, Nur Atiqah; Gisip, Judith (UiTM Press for the Institute of Research Management & Innovation (IRMI), Universiti Teknologi MARA, 2019)
Composite panels were manufactured from kenaf particles and treated with two different alkali treatments using 2% NaOH and 2% KOH with resin contents of 8% and 10% of phenol formaldehyde (PF) at medium density of 650kg/m3. The objectives of this study were to determine the mechanical properties in terms of its modulus of rupture (MOR), modulus of elasticity (MOE) and internal bond (IB), and physical properties namely thickness swelling (TS) and water absorption (WA) of treated kenaf board. The mechanical and physical tests were performed according to the Malaysian Standard (MS1787:2004). The minimum requirements value for MOE, MOR and IB were 2000 MPa, 14 MPa and 0.45 MPa respectively for furniture grade particleboards for use in humid conditions (PF2). According to Malaysian specifications for physical properties, the maximum requirement for thickness swell is 15%. Results indicated that both treated boards with NaOH and KOH showed an increase in strength properties compared to untreated particleboard. Particleboard treated with KOH exhibited the highest MOR and MOE values, while board with NaOH treatment gave the highest IB value. The boards with treated particles gave better performance in terms of physical properties. There were no significant differences in mechanical properties (MOR, MOE and IB) and physical properties for the different alkali treatment. The values of bending strength and IB strength increased with an increase in resin content, while TS and WA increased with a decrease in resin content. In conclusion, NaOH and KOH treated kenaf particles improved board performance and could be considered as an alternative material for particleboard production.